Вторая жизнь: [роман] / Маша Трауб - Трауб Маша (Проза Маши Трауб, 2018)
Экземпляры: РБ (20210413☮) / Инвентарный номер: 61581 / Цена: 50.00 / Сис.шифр: 84(2Роc=Рус)6 / Авт.знак: Т 65 / ГРНТИ: 17.82.31 / ББК: 84(2Роc=Рус)6